Itpka depletion implicates defects in anterior neural development of Xenopus laevis - Saumweber, Ernestine; Becker, Marie-Christine; Kunkel, Sophie; Welke, Jana; Schott, Sandra; Vizinho-Vieira, Christian; Faoual, Selina; Schmeisser, Michael J.; Kühl, Susanne J. (Frontiers in Cell and Developmental Biology, 2025)
Inositol 1,4,5-trisphosphate 3-kinase A (Itpka) is a neuronal isoform of the ITPK family that regulates both actin dynamics and calcium signaling. While itpka deficiency in adult mice mainly results in central nervous system phenotypes, its contribution to early development remains unclear. To study the role of Itpka in embryogenesis, we used the South African clawed frog, Xenopus laevis, as vertebrate model organism. Our analysis revealed that itpka is specifically expressed in distinct regions of the developing anterior neural tissue. To investigate Itpka function during early anterior neural development, we generated a morpholino oligonucleotide (MO)-mediated itpka knockdown approach. The depletion of Itpka leads to defects in head, brain, and eye development which can be rescued by Xenopus itpka RNA co-injection. An analysis of the underlying molecular basis revealed a reduced expression of key genes associated with head, brain and eye development in Itpka MO-injected embryos. These findings highlight a crucial role of Itpka during anterior neural development in Xenopus laevis and indicate that the function of Itpka needs to be further investigated.